2x 5 4 x 1 )- 2 x 3
![2x 5 4 x 1 )- 2 x 3](https://d2vlcm61l7u1fs.cloudfront.net/media/ee5/ee597bc1-a7c0-4393-9b96-05cefe5ed889/phpCeMHO0.png)
- 2x 3 4 x 2 x 1 5 derivative
- 5 2x 1 2 4 x 1 )( x 3 )- 2 5 3x 2
- F x )=( 2x 3 4 x 2 x 1 5
- 2x 5 x 5 3x 4 x 2 1
- 5 2x 3 )( x 2 )- 2 5x 4 )( x 1 )= 75
- 2x 5 x 4 6x 9 x 2 3x 1
- 3 2x 5 )+ 4 x 1 )= 7 x 3 )+ 2 2x 1
- (2x+5)^2 - 4(x+3)(x-3) tại x = 1/20
- 3 4 x 1 2 5 x 3 3x 11 2x
- 4 2x 1 )- 2 x 5 )= 5 x 1 )+ 3 verify
- 2x 5 2 4 x 3 )( 3x tại x 1 10
- Giải pt x 2 )( 3x 5 )=( 2x 4 )( x 1
- 8 4 x 1 )- 5 x 3 )= 2 5 2x